Analisis Perilaku FoMO Mahasiswa Universitas Jember Dalam Perspektif Masyarakat Konsumsi-Baudrillard - Jenny Fernanda; Muhammad Faisal Azka; Achmadiannisa Putri R.A. (Pusat Riset dan Inovasi Nasional, 2023)
FoMO or Fear of Missing Out behavior is a type of behavior that is very widespread these days. The aim of this study is to analyze and dissect the FoMO behavior. In particular, it concerns shoe fashion, which is widespread among students. The existence of different types of faculties spread across universities with the grouping of saintek and soshum certainly has consequences for students. It provides a perspective on a phenomenon. Of course, there are differences between the two large groups. It is this difference that provides an interesting proposition for why this research was conducted. This research uses a qualitative method with a phenomenological approach. The results of the study showed that FoMO behavior has consequences for students buying or consuming goods, especially shoes with brand value. The authenticity of an item also influences students' shopping interest. They prefer to buy original or genuine shoes, which guarantee quality, rather than branded but fake or imitation (KW) shoes. Thus, it can be concluded that there is still relevance between the theory of consumer society by Jean P. Baudrillard and the condition of contemporary students of Jember University.